Mixed immunobullous disease in infants: Falls in bullous pemphigoid-linear IgA spectrum? - Sruthi Mohanan; Sebastian Criton; Usha Mary Abraham (Wolters Kluwer Medknow Publications, 2020)
Bullous pemphigoid (BP) and linear immunoglobulin A bullous dermatosis (LABD) are common immunobullous diseases affecting both adults and children, with minor differences in clinical presentation. The only test for a definitive diagnosis is direct immunofluorescence (DIF) study, with linear deposits of immunoglobulin G (IgG) (mainly) at the dermoepidermal junction (DEJ) being diagnosed as BP and linear deposits of IgA at DEJ, diagnosed as LABD. Mixed immunobullous disease is the term given for immunobullous diseases with equal IgA/IgG deposits at the DEJ. Through this case report, a mixed immunobullous disease with clinical diagnosis of LABD and DIF findings of BP is being discussed. Furthermore, the presence of a BP-LABD spectrum of disease that can progress in either direction and present with features of both diseases is discussed.